Strengthening Halal Tourism Through Local Wisdom: A Maqashid Syariah Analysis of the Yogyakarta Palace - Setiawan bin Lahuri; Inaya Zuhrifa; Ainun Amalia Zuhroh (Universitas Pembangunan Nasional Veteran Jakarta, 2026)
Abstract The Yogyakarta Palace (Karaton Ngayogyakarta Hadiningrat) is a key cultural tourism spot. However, the global growth of halal tourism has highlighted some issues related to its application at heritage sites. There are limited halal facilities, and there are worries about cultural commodification. This situation creates a need to examine how the palace's local wisdom relates to Shariah principles. While earlier research mainly looked at halal tourism from regulatory, marketing, or destination management perspectives, this study provides a fresh take. It combines local wisdom in cultural heritage tourism with a Maqashid Syariah framework. The study focuses on halal tourism development strategies based on local wisdom and evaluates them through the lens of Maqashid Syariah. Researchers used a qualitative approach, including cultural observation, in-depth interviews, and thematic analysis based on the Miles and Huberman model. The findings indicate that tourism practices at the palace meet the standards set by DSN-MUI Fatwa No. 108/2016 and national halal tourism strategies. Five dimensions of local wisdom customs, architecture, arts, traditional attire, and the Javanese language embody Islamic values and foster public welfare, character development, and economic empowerment. This study adds to theory by showing how Maqashid Syariah can be an evaluative tool to balance cultural preservation with halal tourism growth in heritage sites. Combining these elements offers a sustainable and culturally grounded model for halal tourism development that can be applied to other heritage tourism contexts. Abstrak Karaton Ngayogyakarta Hadiningrat merupakan destinasi wisata budaya yang banyak diminati, namun tren pariwisata halal global masih menghadapi ambiguitas penerapan pada situs heritage, termasuk keterbatasan fasilitas halal dan kritik terhadap komodifikasi budaya. Kondisi ini menimbulkan kebutuhan untuk menilai sejauh mana kearifan lokal karaton dapat selaras dengan prinsip syariah. Penelitian ini bertujuan menganalisis strategi pengembangan pariwisata halal berbasis kearifan lokal di Karaton Ngayogyakarta dan mengevaluasinya melalui perspektif Maqashid Syariah. Metode yang digunakan adalah pendekatan kualitatif melalui observasi budaya, wawancara mendalam, dan analisis tematik Miles Huberman. Hasil penelitian menunjukkan bahwa praktik wisata karaton telah sesuai dengan Fatwa DSN-MUI No. 108/2016 serta strategi halal Kemenparekraf. Lima dimensi kearifan local adat, arsitektur, kesenian, busana adat, dan bahasa Jawa merefleksikan nilai Islam dan mendukung kemaslahatan, pendidikan karakter, serta pemberdayaan ekonomi. Integrasi ini menawarkan model pengembangan pariwisata halal berbasis budaya yang berkelanjutan.